2012
DOI: 10.1186/1471-2407-12-373
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of microsatellite instability and loss of heterozygosity in three loci in breast cancer patients receiving chemotherapy: a prospective study

Abstract: BackgroundThe aim of the study was to evaluate potential chemotherapy-induced microsatellite instability, loss of heterozygosity, loss of expression in mismatch repair proteins and associations with clinical findings in breast cancer patients, especially resistance to chemotherapy and/or development of other tumors in the four years following chemotherapy treatment.MethodsA comprehensive study of chemotherapy-related effects with a follow-up period of 48 months post treatment was conducted. A total of 369 peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
2
12
0
1
Order By: Relevance
“…The microsatellite TP53ALU was initially found to be a polymorphism locus that had been frequently used as a marker in previous studies (10,11). Consistently, we observed 9 genotypes of TP53ALU in normal tissues and confirmed that TP53ALU is a highly polymorphic pentanucleotide repeat microsatellite.…”
Section: Discussionsupporting
confidence: 88%
“…The microsatellite TP53ALU was initially found to be a polymorphism locus that had been frequently used as a marker in previous studies (10,11). Consistently, we observed 9 genotypes of TP53ALU in normal tissues and confirmed that TP53ALU is a highly polymorphic pentanucleotide repeat microsatellite.…”
Section: Discussionsupporting
confidence: 88%
“…In humans, a strong correlation was found between LOH events and deficient protein expression of specific genes and the incidence of secondary tumors of breast cancer (Kamat et al, 2012). LOH/LOA on specific chromosomal regions was reported to contribute to the molecular pathway of glioma progression in Malay population (Zainuddin et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of studying these instabilities is emphasized by the role MSI and LOH play in the early stages of tumorigenesis and cancer development [ 22 - 24 ]. The assessment of MSI and LOH may carry a predictive value for earlier detection and management of secondary tumors [ 37 , 41 ]. Since previous reports indicate that the use of 10 markers is optimal, the present study used a panel of five microsatellites recommended by the NCI guidelines and another five markers of our choosing [ 42 - 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-related MSI and LOH have been analyzed in a few studies in recent years, highlighting the importance of screening patients for these genomic instabilities after chemotherapy completion [ 35 - 37 ]. Consequences of MSI and LOH that were observed in these studies included increased resistance to chemotherapy, recurrence of primary tumors, and/or appearance of secondary malignancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation